Experimental investigation of shear strength of concrete beams with recycled concrete aggregates. (1st January 2011) - Al-Zahraa, Fatma; El-Mihilmy, Mahmoud T.; Bahaa, Tarek
In recent years, the amount of waste being generated is on the rise that may lead to waste disposal crisis. One solution for this problem is the use of concrete waste as a course aggregate in casting fresh concrete members. In this paper, experimental shear tests on concrete beams with recycled concrete coarse aggregates were conducted. Twelve beams with different percentage of recycled concrete aggregates, shear reinforcement and shear spans were tested under two concentrated loads up to failure. Data presented include the deflection characteristics, steel strains, cracking behaviour and ultimate loads. Tests results indicated that for low amount of recycled aggregates, the shear strength is almost the same as the reference beams. In some cases beams with recycled concrete aggregates give higher failure load than beams with normal concrete aggregates. However, for high percentage of substation, the experimental loads were less than the beams with natural aggregates. The ACI shear design procedure was examined to investigate its validity for designing beams with recycled concrete. The predicted values of 38 beams were conservative compared to the experimental values and subsequently can be used in case of beams with recycled concrete.